Optimizing the Digital Marketing Strategy of Nasi Krawu MSMEs in Increasing Competitiveness and Sales Turnover in the Digital Era - Sugiantoro, Bagus; Hakimah, Ema Nurzainul (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study aims to analyze the digital marketing strategies implemented by Nasi Krawu MSMEs in increasing competitiveness and sales turnover, as well as identifying relevant digital marketing optimization strategies in the digital era. Design/Method/Approach : This research uses a qualitative descriptive approach. Data was collected through in-depth interviews with Nasi Krawu MSME owners, employees, and consumers, as well as direct observation of digital marketing activities carried out. The analysis was carried out thematically with triangulation of approaches to ensure the validity of the data. Research Findings : The study found that digital marketing strategies through social media such as Facebook and WhatsApp, as well as messaging platforms such as GrabFood and GoFood, are effective in increasing product visibility and appeal. The implementation of creative content such as promotional videos and special discounts also contributes to increased customer loyalty and turnover sales. However, the limitations of digital knowledge and product durability are significant challenges. Theoretical contribution/originality: this study enriches the literature on digital marketing in the traditional culinary MSME sector, with the emphasis on the importance of technology adaptation in the face of market competition in the digital era. Practitioner/Policy Implications: This study provides practical guidance for MSMEs to optimize digital marketing strategies and recommends increasing digital literacy for small business actors. The government and related institutions are also expected to provide training and infrastructure support to support the transformation of digital MSMEs. Research limitations : This research is limited to one research object, namely Nasi Krawu MSMEs, so the results cannot be generalized to other sectors. Further research can include different types of MSMEs to understand the broader pattern of digital marketing implementation.